Association between cognitive diagnosis and a range of significant life events in an elderly essential tremor cohort: a longitudinal, prospective analysis - Berry, Diane S.; Nguyen, Diep; Cosentino, Stephanie; Louis, Elan D. (Frontiers in Neurology, 2023)
Background Although essential tremor (ET) patients have greater odds of mild cognitive impairment (MCI) and dementia than age-matched controls, the functional consequences of these enhanced odds are unknown. We examined associations between cognitive diagnosis and the occurrence of near falls, falls, use of a walking aid or a home health aide, non-independent living, or hospitalizations within a prospective, longitudinal study of ET patients. Methods A total of 131 ET patients (mean baseline age = 76.4 ± 9.4 years) completed a battery of neuropsychological tests and questions about life events and were assigned diagnoses of normal cognition (NC), MCI, or dementia at the baseline and at 18-, 36-, and 54-month follow-ups. Kruskall–Wallis, chi-square, and Mantel–Haenszel tests assessed whether the diagnosis was associated with the occurrence of these life events. Results Patients with final diagnoses of dementia were more often reported as living non-independently than NC or MCI patients and more often used walking aids than NC patients, with a p-value of <0.05. Patients with a final MCI or dementia diagnosis more often employed a home health aide than NC patients, with a p-value of <0.05. Moreover, Mantel–Haenzsel tests revealed linear associations between the occurrence of these outcomes and the level of cognitive impairment, with a p-value of <0.001 (i.e., dementia > MCI > NC). Conclusion Cognitive diagnosis was associated with reported life events of ET patients, including the use of a mobility aid, employment of a home health aide, and removal from an independent living situation. These data provide rare insights into the important role cognitive decline plays in the experiences of ET patients.